Resilience personality profiles among Swedish long‐term unemployed. Issue 4 (16th June 2021) - Granjard, Alexandre; Garcia, Danilo; Rosenberg, Patricia; Jacobsson, Christian; Cloninger, Kevin M.; Cloninger, Claude Robert
Abstract: Our aim was to investigate the prevalence of resilience personality profiles in a sample of Swedish long‐term unemployed in relation to the general Swedish population. We found that only 1.50% (vs. 26% in the general population) in the long‐term unemployed sample had a resilient personality profile, that is, low in harm avoidance (e.g., relaxed and optimistic), high in persistence (e.g., hard‐working), and high in self‐directedness (i.e., goal‐oriented and resourceful).